Ultrastrong Graphene Absorption Induced by One-Dimensional Parity-Time Symmetric Photonic Crystal - Peichao Cao; Xiangbo Yang; Shiqi Wang; Yuehua Huang; Nana Wang; Dongmei Deng; Chengyi Timon Liu (IEEE Photonics Journal)
A novel microcavity structure based on 1-D parity-time (PT) symmetric photonic crystal (PC) is presented to get the embedded monolayer graphene absorption enhanced significantly, which paves a path to achieve ultrastrong, controllable, and anisotropic graphene absorption for incident eigenfrequency wave from near infrared to visible. When oscillation of absorption is at the center of the PT broken phase, because of exact matching usage of gain and loss modulation, and singular strong coupling effects that are induced by the PT symmetric PC behind graphene layer, ultrastrong and nonreciprocal graphene absorption can be obtained, and the maximum could reach the order of 10 $^5$ . This approach offers a way to improve the responsivities of graphene-based optodetectors and even to the design of direction sensitive graphene optical communication components.